2010
DOI: 10.1080/09613211003729988
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of urban and rural housing stocks in China

Abstract: The massive migration flows from rural to urban areas in China, combined with an expected decline in the total population over the next decades, leads to two important challenges for China's housing: the growth of its urban housing stock and the shrinkage of rural housing. The rural and urban housing systems in China were analyzed using a dynamic material flow analysis model for the period 1900-2100 for several scenarios assuming different development paths for population, urbanization, housing demand per capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 30 publications
2
86
1
Order By: Relevance
“…Based on the previous, region-specific references, we estimate concrete service life (t l ) in China is 35 years (ranging from 4-73 years), the duration of the demolition stage (t d ) is 0.4 years (ranging from 0.1-0.8 years), and the duration of the secondary use stage (t s ) is 64.6 years 36,37 . In Europe, service life is estimated to be 70 years (ranging from 50-90 years), demolition stage is 0.4 years (ranging from 0.1-0.7 years), and secondary use stage is 29.6 years 18,24 .…”
Section: Service Life Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous, region-specific references, we estimate concrete service life (t l ) in China is 35 years (ranging from 4-73 years), the duration of the demolition stage (t d ) is 0.4 years (ranging from 0.1-0.8 years), and the duration of the secondary use stage (t s ) is 64.6 years 36,37 . In Europe, service life is estimated to be 70 years (ranging from 50-90 years), demolition stage is 0.4 years (ranging from 0.1-0.7 years), and secondary use stage is 29.6 years 18,24 .…”
Section: Service Life Durationmentioning
confidence: 99%
“…Specifically, relative humidity, ambient CO 2 concentration 35,36 , and additives have been shown to affect carbonation rate coefficients 25 . The range of applicable conditions are estimated based on the previously referenced, region-specific studies and survey statistics 9,18 .…”
Section: Concrete Strength Classesmentioning
confidence: 99%
“…Wang et al (2016) presented a snapshot of country-wide cement and concrete material cycle in China based on general MFA method. Considering the time effect, dynamic MFA models were established to simulate the long-term evolution of building stock (Hu et al, 2010b), to estimate the history cement consumption and to forecast the future cement demand of building subsystem (Huang et al, 2013). In terms of city scale, cement consumption in residential building system (Hu et al, 2010a) and road system (Guo et al, 2014) were accounted as well.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Rauch et al, the total steel stock for the Beijing municipality was reported to be 29. 4 Mt for 2000 14) . Nevertheless, the total of estimated civil engineering/building steel stock in the Beijing municipality was estimated to be 84. .…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al tried to estimate the housing stocks using dynamic material flow analysis modeling for the period of 1900-2100 by top-down approach [4]. This work was then extended to estimate the iron and steel stock of the buildings [1].…”
Section: Introductionmentioning
confidence: 99%